Physical and Mechanical properties of glass composite material made from incinerated scheduled waste slag and SLS waste Glass - Jariah, Mohamad Juoi; Zulkifli, Mohd Rosli; Toibah, Abd Rahim; Siti Rahmah, Shamsuri (Trans Tech Publications, 2013)
Incineration of scheduled waste and landfilling of the incineration residue (Bottom Slag) is extensively practised in Malaysia as a treatment method for scheduled waste. Land site disposal of Bottom Slag (BS) may lead to environmental health issues and reduces the availability of land to sustain the nation’s development. This research aims in producing Glass Composite Material (GCM) incorporating BS and Soda Lime Silicate (SLS) waste glass as an alternative method for land site disposal method and as an effort for recycling SLS waste glass .SLS waste glass originates from the urban waste and has been a waste stream in most of the nation whereby the necessity for recycling is in high priority.The effect of BS waste loading on the GCM is studied.Batches of powder mixture is formulated with 30 wt% to 70 wt % of BS powder and SLS waste glass powder for GCM sintering.The powder mixtures of BS and SLS waste glass is compacted by uniaxial pressing method and sintered at 800⁰C with heating rate of 2⁰C/min and 1 hour soaking time. Physical analysis of bulk density, apparent porosity, and water absorption is perfomed according to ASTM C-373 standard. Mechanical testing of microhardness vickers according to ASTM C1327 and Modulus of Rupture (MOR) according to ISO 10545-4 is conducted. Microstructural analysis is carried out using Scanning Electron Microscope and phase analysis by X-ray diffraction method.Phases identified are Anorthite sodian,Quartz,Hematite and Diopside from X-ray diffraction analysis. Higher BS waste loading shows weak physical and mechanical properties .GCM from batch formulation of 30 wt % BS and 70 wt% SLS waste glass has projected optimized physical and mechanical properties. It is observed this batch has projected lowest water absorption percentage of 1.17 % , lowest porosity percentage of 2.2 %, highest bulk density of 1.88 g/cm3 and highest MOR of 70.57 Mpa and 5.6 GPa for Vickers Microhardness.